PENGARUH SISTEM PENGGAJIAN DAN PENGUPAHAN TERHADAP EFEKTIFITAS KINERJA KARYAWAN OUTSOURCING - Trisnawati, Santi Dwi; Ngumar, Sutjipto (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to test empirically about the influence of the application ofpayrollsystem to theeffectiveness of the performance of the company. The data collection has been done by performingdocumentation, observation and issuing questionaires. The multiple linear regressions are used as theresearch method, the collected data in the form of interval data which uses the score measurement fromone to five. The samples are 80 employees. The result of the test shows that simultaneously themultiple determinationcoefficients (R2) variable in the payroll system has influence to the effectivenessof the performance of the employees. The result of partial test shows that the variable in the payrollsystem in the human resources management which consists of assigning task, providingcompensation, providing health insurance and security, and performing voluntarily dismissal orfiring the employees have influence to the effectiveness of the performance of the company. Meanwhile,recruiting and employing new employees, give training to the employees, and evaluating theperformance of the employees do not have any influence to the effectiveness of the performance of theemployees.Keywords: payroll system, effectiveness of performance of employees